Pricing Of Options In Indian Derivative Market: An Empirical Analysis - Dr. Swapna.H.R, Dr. Arpana. D, Dr.M. Venkataramana Reddy (International Journal of Advanced Science and Technology, 2020)
There has been tremendous growth in the use of financial derivative Instruments. The equity derivative include stock options, index options, stock futures and index futures. Among these products the growth rate of index options is remarkable due to risk management and trading the option pricing models occupied an important place in derivatives market. In the process of pricing correct pricing is very important to take a decision whether to buy or sell. There are different pricing models such as hall and White model, model of Heston and so on, but for this study Black and Scholes model is used, since it is the most Universally accepted model in pricing options. The main objective of the study is to determine the theoretical price of stock option using Black and Scholes model, Blacks model and Binomial option pricing model with theoretical and GARCH space volatility. The study also tries to find out if there is a significant difference between model price and actual market price of an option. GARCH volatility was used in these models which resulted in over estimating most of the stock premiums. The present study will have an influence on various groups in the financial market like investors and finance managers.